'As línguas têm de estar no seu devido lugar' ('languages have to be in their proper place'): language ideologies, languagised worlds of schooling and multilingual classroom practices in Timor-Leste. Issue 1 (1st January 2019) - da Costa Cabral, Ildegrada
ABSTRACT: This paper contributes to the building of a sociolinguistics of the south by considering the nature and significance of contemporary language-in-education policy processes in Timor-Leste, and by tracing the ways in which these processes have been shaped by its specific colonial and post-colonial history. In presenting this account, I draw on recent research of a linguistic ethnographic and historical nature conducted in Timor-Leste. The linguistic ethnographic research included observation, audio-recording and analysis of multilingual classroom interaction, interviews with teachers, interviews with elite social actors who have been closely involved in the planning and implementation of language-in-education policy in the period following Independence in 2002. This paper takes a longue durée perspective, tracing the political, sociolinguistic and educational history of Timor-Leste. I argue for the need to chart out new directions in critical, ethnographic studies of language-in-education policies in the global south, incorporating perspectives on colonialism and coloniality, and taking account of local situated practices in schools and classrooms, along with the different language values and understandings of different social actors – values and understandings that have been shaped by wider political and ideological processes and by their positioning vis-á-vis these processes.